The Impact of Covid-19 On Social Responsibility: The Case of Fashion Industry - Dawid GARSTECKI; Karolina KWIECIŃSKA (Communications of International Proceedings, 2021)
CSR is has been often accused of being hidden marketing activities. It can be stated that COVID-19 pandemic is a kind of test for companies' declarations about CSR activities. Moreover some researchers questioning whether the CSR actions which have been taken by companies during the coronavirus pandemic are  truly responsible. Some argue that these activities are ad hoc, temporary reaction to the current situation. The purpose of this paper is to outline the impact of COVID-19 on fashion industry social responsibility. The results suggest that it is too early to provide a definite answer to a question whether the companies CSR activities in the time of COVID-19 pandemic are authentic or they are only a temporary actions caused by pandemic. The answer to this question will be the subject of future study.
Keywords: Corporate Social Responsibility; Fashion Industry; COVID-19.